2017
DOI: 10.1016/j.ijfatigue.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Plasma immersion ion implantation: Influence on the rotating bending fatigue strength of AA 7050-T7451 aluminum alloy

Abstract: Failures in structural components due to cyclic loading are associated with the surface damage. The aircraft industry has been searched into the alternative coatings that enhance performance by reducing the environmental impact. Coatings deposited by different surface processes are more or less effective to improve fatigue life of diverse elements. The sulphuric and chromic anodizing methods were applied on AA 7050-T7451 aluminum alloy. The study results were compared with the plasma immersion ion implantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…High frequencies result in higher operating temperatures and the heat increases the instability of the nitride layer, formed on surface, due to thermal stress [33]. Minto et al [18] studied the fatigue behavior of AA7050 aluminum alloy, treated by PIII with nitrogen, varying the voltage parameters (5-10 kV) and frequency (100-1000 Hz). They performed XRD, microhardness, microscopy, EDS and residual stress analysis of the different experimental conditions and related to the rotating bending fatigue behavior.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…High frequencies result in higher operating temperatures and the heat increases the instability of the nitride layer, formed on surface, due to thermal stress [33]. Minto et al [18] studied the fatigue behavior of AA7050 aluminum alloy, treated by PIII with nitrogen, varying the voltage parameters (5-10 kV) and frequency (100-1000 Hz). They performed XRD, microhardness, microscopy, EDS and residual stress analysis of the different experimental conditions and related to the rotating bending fatigue behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, PIII treatments conducted at higher frequencies decreased fatigue resistance of aluminum alloy, although generating compressive residual stresses on surface. Finally, the authors observed that even if the voltage dropped, if the frequency increases, the fatigue resistance of aluminum alloy decreases, making the frequency parameter a predominant influence on microstructure and mechanical behavior [18]. Bonora et al [17] treated 15-5PH stainless steel with nitrogen by PIII.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent papers showed that PIII treatment increases the fatigue life of steels and aluminum alloys, both applied as landing gear components [28,29]. And when this treatment had a deleterious effect on the fatigue behavior compared to the base material, this drop in performance was lower than that caused by other more conventional surface treatments [25,29,30,31].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the AlN layer can be formed by low-cost nitriding methods such as the in situ forming technique. This idea has inspired several teams worldwide to prepare AlN layers on aluminum and its alloys through nitrogen plasma-assisted nitriding treatments, such as the plasma immersion ion implantation (PIII) method [5,6], electron cyclotron resonance (ECR) plasma method [7][8][9], plasma enhanced chemical vapor deposition method [10], plasma activated physical vapor deposition (PAPVD) method [11], and thermionic arc discharge method [12].…”
Section: Introductionmentioning
confidence: 99%